Comparación del sellado corono-apical de dos materiales de restauración temporal - Zavala Enríquez, Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
The function of the cements of temporary obturation is the one of preventing the contamination of the conduits radiculares during and after the endodoncia treatment for nutritious remains, oral fluids and microorganisms. A material of obturation temporary ideal should provide a good one sealed in the structure it would jag, to avoid the marginal microfiltration, not to present porosities, to possess levels of dimensional variation to the thermal similar changes to the tooth, good resistance to the abrasion and the compression, placement easiness and removal, compatibility with the material intraconducto and aesthetic good aspect.

La función de los cementos de obturación temporal es el de prevenir la contaminación de los conductos radiculares durante y después del tratamiento de endodoncia por restos alimenticios, fluidos orales y microorganismos. Un material de obturación temporal ideal debe proporcionar un buen sellado en la estructura dentaria, evitar la microfiltración marginal, no presentar porosidades, poseer niveles de variación dimensional a los cambios térmicos similares al diente, buena resistencia a la abrasión y a la compresión, facilidad de colocación y remoción, compatibilidad con los materiales intraconducto y buen aspecto estético
Facultad de Odontología. Especialidad en Endodoncia
Keywords: info:eu-repo/classification/cti/3; FO-E-2011-0002; Cementos; Obturación; Conductos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4507